2019
DOI: 10.1016/j.amsu.2019.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of treatment methods of appendiceal mass and abscess: A prospective Cohort Study

Abstract: BackgroundThe aim of our prospective study is to compare and analyze the results of two treatment methods of appendiceal mass and abscess: emergency surgery and conservative treatment with and without interval surgery.Materials and methods74 Patients with the diagnosis of appendiceal mass or abscess were enrolled in this study. The patients were assigned into two groups: the emergency surgery group and the conservative management group. The conservative management group was subdivided into two groups: interval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 27 publications
0
29
0
3
Order By: Relevance
“…1 for the procedure of literature selection), of which 845 patients were treated surgically (group IO) and 756 patients were treated conservatively (group CM). A total of 4 randomized controlled studies (RCT) [20][21][22][23] were included, and 10 retrospective studies (RS) [24][25][26][27][28][29][30][31][32][33] were included. The literature information of major concern is shown in the following table (Table 1)…”
Section: Data Analysis and Processingmentioning
confidence: 99%
See 4 more Smart Citations
“…1 for the procedure of literature selection), of which 845 patients were treated surgically (group IO) and 756 patients were treated conservatively (group CM). A total of 4 randomized controlled studies (RCT) [20][21][22][23] were included, and 10 retrospective studies (RS) [24][25][26][27][28][29][30][31][32][33] were included. The literature information of major concern is shown in the following table (Table 1)…”
Section: Data Analysis and Processingmentioning
confidence: 99%
“…A total of 10 studies 21,22,[24][25][26][27]29,30,32,33 reported the occurrence of unplanned interventions during treatment in each group (Fig. 2.…”
Section: Unplanned Additional Interventionmentioning
confidence: 99%
See 3 more Smart Citations